The representations and functions of youth and young people in Early Medieval English literature - Giancoli, Chiara (2023)
While childhood and old age in Early Medieval England have already been studied, youth has received relatively little attention. This thesis aims to be the first (to my knowledge) study of youth in Early Medieval English literature. It explores how youth was represented in wisdom poetry (Chapter 2), hagiography (Chapter 3), and heroic verse (Chapter 4), and how it was employed: how did the descriptions of youth and young people contribute to the values in these texts? What themes did youth convey? For the purposes of this thesis, youth is understood in two ways: as a ‘period of growth’, that is as a period of personal, intellectual, and moral development between childhood and adulthood, discussed in chapters 2-4, and as a period of ‘youthfulness’, which does not entail any development (but still conveys textual values) in the Vita Bonifatii and The Wanderer (Chapter 5). Chapter 1, instead, functions as an introduction to the thesis, including a literature review on youth in medieval studies, interpretations of the concept of the ‘ages of man’ in Early Medieval English sources, terminology relating to youth and young people in Old English and Latin dictionaries, and provides an overview of my aims and methodology. In this way, I want to show that youth illustrated significant textual ideas: for instance, it conveyed Christian teachings in hagiography and heroic values in heroic poetry; but there were also important differences within the same genre, or even within the same text, which show that authors described and employed youth and young people according to their own purposes. Therefore, this thesis demonstrates that youth was an important theme in Early Medieval English literature, which occurs in a variety of texts and conveys different values, and it might help to understand better Early Medieval English literary sources.